Differences between winning and defeated top quality basketball teams in final tournaments of European club championship - Trninic, S.; Dizdar, D.; Lukic, E. (Collegium Antropologicum, 2002)
The goal of this research was to identify parameters among the 12 indicators of situation-related efficiency that differentiated between the winning and defeated top quality teams which played in final tournaments of the European club championships from 1992 to 2000. The differences were confirmed by discriminant analysis, although the canonical correlation was here somewhat lower than in the previous similar research studies done on the so-called regular season games. The probable reason for the smaller differences obtained in the present study may be found in almost equal (high) quality of the teams competing in Final Fours. The highest discriminative power was obtained in the variable defensive rebounds, then in the variables field goal percentage and free throw percentage, whereas the variable assist had evidently smaller impact with regard to the referent studies. The obtained results suggested that the winning teams showed more of tactical discipline and responsibility in controlling inside positions for defensive rebounds, as well as in controlling play on offense and the ball until the required open shot chance, which considerably reduced game risks and resulted in a lower number of turnovers and in a higher shooting percentage. Such a type of decision-making in play require a high degree of reciprocal help of players on both defense and offense and a higher level of concentration and self-confidence when shooting field goals and free throws. The common denominator of the winning teams was a lower number of imbalanced states in their play (the organized style of play on defense and offense implied) and a higher level of collective outplaying the opponents with the controlled system of play, which enabled entire potential of the victorious teams to be expressed.